Industrial Automation and Edge Computing SCADA PLC PAC IO-LINK-2 - Topaloğlu, Fatih (Fırat University, 2021)
Increasing interest in Industry 4.0 applications has brought with it many new technologies and strategies for processing all kinds of production-related data, which are at the center of this trend. Although many of these technologies are not very new, they have not yet reached sufficient recognition in the industry. The term edge computing is among the concepts that need to be clarified in this context. Edge computing draws local intelligence and data processing capability to the parts of the communication network close to the end devices such as pumps, motors, sensors, relays that produce data, and performs the analysis of the data without the need to transfer it somewhere. However, this process also has difficulties. Edge computing architectures in industrial applications need to address bandwidth, management complexity, latency, and network security risks. With this study, four important architectural solutions that help to optimize resource usage on the edge computing platform for industrial applications are proposed and analyzed.
Keywords: Engineering; Mühendislik